Organic Acid and Nutrient Composition of Lactic Acid Bacteria Inoculated Total Mixed Ration Silage under Tropical Condition: Organic Acids and Nutrients Composition of Lactic Acid Bacteria - Wahyudi, Ahmad; Pamungkas, Dicky; Setyobudi, Roy Hendroko; Hendraningsih, Listriari; Vincēviča-Gaile, Zane (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
Organic acids and nutrients composition of total mixed ration (TMR) silage inoculated with local Lactic acid bacteria (LAB) derived from paddy rice was studied. This study was conducted to prepare TMR silage in tropical climate. LAB was isolated from local paddy rice that was planted around Muhammadiyah University of Malang, East Java, Indonesia. The local LAB ability was compared with commercial strain L. plantarum FCC 123 for organic acids and nutrients composition on TMR silage fermentation. The study was designed by completely randomized with five treatments (T0: TMR silage without LAB, T1: TMR silage + L. plantarum FCC 123, T2: TMR silage + local LAB Ciherang 1, T3: TMR silage + local LAB Membramo 1, T4: TMR silage + local LAB Rajalele 1), each treatment was replicated four times. This study showed the inoculation of local LAB in TMR silages preparation significantly (P ≤ 0.01) increased lactic acids production and tended to reduce acetic acid and pH value compare to control. There were not different all treatment and control on nutrients composition. It could be concluded that the local LAB inoculant had ability similar to L.plantarum FCC 123 on improving quality of TMR silage.